A new genus and three new species of Phyllocoptini (Acari: Eriophyidae: Phyllocoptinae) from the Qinling Mountains, Shaanxi Province, northwestern China - Xue, Xiao-Feng; Song, Zi-Wei; Hong, Xiao-Yue (Zootaxa, 2006)
A new genus and three new species of eriophyid mites from the Qinling Mountains, Shaanxi Province, northwestern China are described and illustrated: Calvittacus regiae gen. nov. and sp. nov. on Juglans regia L. (Juglandaceae); Calepitrimerus dendrobenthamiae sp. nov. on Dendrobenthamia japonica var. chinensis (Osborn) Fang (Cornaceae) and Calepitrimerus fopingi sp. nov. on Lindera glauca (Sieb. et Zucc.) Blume (Lauraceae). All the species are vagrant on the undersurface of leaves. No apparent damages were found on the host plant. A key to the species of Calepitrimerus from China is provided.